1994
DOI: 10.1177/42.9.8064132
|View full text |Cite
|
Sign up to set email alerts
|

Simple mucin-type carbohydrate antigens in major salivary glands.

Abstract: (4A3423).Simple mucin-type catbohydrate antigens Tn, sialaql-Tn and T are often markets of neoplastic transformation and have very limited expression in normal tissues. We performed an immunohistological study of simple mucin-type carbohydrate antigens, including H and A variants, with well-defined monoclonal antibodies (MAb) on frozen and paraffinembedded normal salivary gland tissue from 22 parotid, 14 submandibular, six sublingual, and 13 labial glands to elucidate the simple mucin-type glycosylation pattem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…Our results are in agreement with other authors who described the absence of TF in selected tissues like uterus, colon, urothelium or squamous cells (Ravn and Jensen 1988;Mandel et al 1991;Itzkowitz 1992;Langkilde et al 1992). Philipsen et al (1991), Therkildsen et al (1994), and Carneiro et al (1994) reported the presence of TF in acinar cells of pancreas, in salivary glands, and in the stomach, respectively, employing mAbs HH8 and HB-T1. We have not seen TF in these tissues, either with mAb G/A7, HH8 or HB-T1.…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…Our results are in agreement with other authors who described the absence of TF in selected tissues like uterus, colon, urothelium or squamous cells (Ravn and Jensen 1988;Mandel et al 1991;Itzkowitz 1992;Langkilde et al 1992). Philipsen et al (1991), Therkildsen et al (1994), and Carneiro et al (1994) reported the presence of TF in acinar cells of pancreas, in salivary glands, and in the stomach, respectively, employing mAbs HH8 and HB-T1. We have not seen TF in these tissues, either with mAb G/A7, HH8 or HB-T1.…”
Section: Discussionsupporting
confidence: 96%
“…Tn expression in some epithelial tissues, for instance salivary gland, stomach, and uterus, has been described previously (Carneiro et al 1994;Tashiro et al 1994;Therkildsen et al 1994). In the present study, other epithelial tissues like small intestine were also found to be positive for Tn.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The finding that MG1 and MG2 are synthesized in different cell types is in accordance with previous reports indicating that different carbohydrate side-chains are attached to the protein cores of MG1 and MG2 (Reddy et al, 1985;Prakobphol et al, 1993), since immunohistological data using MAbs defining different carbohydrate epitopes suggest that the pattern of glycosylation is different in mucous and serous cells (Hamper et al, 1986;Therkildsen et al, 1994).…”
Section: Strategy For Production Of Antibodiessupporting
confidence: 90%
“…Moreover, sialyl-T and T antigen can be used as biomarkers in progression of several carcinomas [3649]. The antigens have been found to be expressed in gastric carcinomas such as colon cancer [37, 39], breast carcinomas [43, 50], salivary gland carcinomas [38, 4549], cancer of the human cervix [36], pancreatic tumors [42], ovarian tumors [44] and skin tumors [40, 41]. Since many of these cell types also over-express CD24 [20–22], it is intriguing that the CD24 over-expression may account for the increased sialyl-T in the cancer cells.…”
Section: 0 Results and Discussionmentioning
confidence: 99%